Establishment of Pediatric Cardiac Intensive Care Advanced Practice Provider Services. (January 2016) - Gilliland, Jill; Donnellan, Amy; Justice, Lindsey; Moake, Lindy; Mauney, Jennifer; Steadman, Page; Drajpuch, David; Tucker, Dawn; Storey, Jean; Roth, Stephen J.; Koch, Josh; Checchia, Paul; et al.
The addition of advanced practice providers (APPs; nurse practitioners and physician assistants) to a pediatric cardiac intensive care unit (PCICU) team is a health care innovation that addresses medical provider shortages while allowing PCICUs to deliver high-quality, cost-effective patient care. APPs, through their consistent clinical presence, effective communication, and facilitation of interdisciplinary collaboration, provide a sustainable solution for the highly specialized needs of PCICU patients. In addition, APPs provide leadership, patient and staff education, facilitate implementation of evidence-based practice and quality improvement initiatives, and the performance of clinical research in the PCICU. This article reviews mechanisms for developing, implementing, and sustaining advance practice services in PCICUs.